Associations between cognitive impairment and computed tomography perfusion in different lobes in acute stroke of the anterior circulation - Mengna Chu; Bin Dong; Chao Huang (Arquivos de Neuro-Psiquiatria)
Background Cognitive impairment (CI) during the acute phase of stroke should not be ignored. The present study analyzed the relationship between computed tomography perfusion (CTP) in different lobes and CI during the acute phase of stroke in patients with cerebral infarction. Methods The present study included 125 subjects: 96 in the acute phase of stroke and 29 elderly healthy subjects as a control group. The Montreal Cognitive Assessment (MoCA) was used to evaluate the cognitive status of the two groups. The CTP scans include four parameters: cerebral blood flow (CBF), cerebral blood volume (CBV), time to peak (TTP), and mean transit time (MTT). Results The MoCA scores for naming, language and delayed recall significantly decreased only in patients with left cerebral infarctions. The MTT of the left vessels in the occipital lobe and the CBF of the right vessels in the frontal lobe were negatively related to the MoCA scores of patients with left infarction. The CBV of the left vessels in the frontal lobe and the CBF of left vessels in the parietal lobe were positively linked to the MoCA scores of patients with left infarction. The CBF of the right vessels in the temporal lobe was positively related to the MoCA scores of patients with right infarction. Finally, the CBF of the left vessels in the temporal lobe was inversely correlated with the MoCA scores of patients with right infarctions. Conclusion During the acute phase of stroke, CTP was closely associated with CI. Changed CTP could be a potential neuroimaging biomarker to predict CI during the acute phase of stroke.